2009
DOI: 10.1016/j.neulet.2009.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction attenuates amyloid deposition in middle-aged dtg APP/PS1 mice

Abstract: Caloric restriction (CR) mitigates neurological damage arising from aging and a variety of other sources, including neuropathology in young adult mice that express single and double transgenic (tg) mutations associated with Alzheimer disease (AD). To evaluate the potential of CR to protect against relatively heavy AD-type pathology, middle-aged (13-14 month-old) mice that co-express two mutations related to familial AD, amyloid precursor protein (APP) and presenilin 1 (PS1), were fed balanced diets with 40% fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 45 publications
6
74
1
Order By: Relevance
“…Such neuroprotective effects have been demonstrated in some earlier reports (1,2,4,5,7,(28)(29)(30). The precise mechanisms mediating these beneficial effects of diet restriction are still unresolved though many hypotheses have been considered so far.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Such neuroprotective effects have been demonstrated in some earlier reports (1,2,4,5,7,(28)(29)(30). The precise mechanisms mediating these beneficial effects of diet restriction are still unresolved though many hypotheses have been considered so far.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies suggest that DR may enhance brain functions including learning and memory (3)(4), synaptic plasticity (5), and neurogenesis (6). The precise mechanisms mediating such beneficial effects of DR are still unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…For the area fraction probe (frame 25 μm × 25 μm; guard zone 2 μm, interframe interval 400 μm), the user clicked on the grid points that touched myelin fibers in sections stained with MBP. The area fraction of myelination was quantified as the ratio of product of the area per point and number of points hitting reference area [a(point)· ΣP ref ] over the product of the area per point and number of points hitting the sampled area [a(point)· ΣP samp ], as reported (Buser et al, 2012; Mouton et al, 2009). Sampling continued until the coefficient of error (CE) was less than 0.10.…”
Section: Methodsmentioning
confidence: 99%
“…Sampling continued until the coefficient of error (CE) was less than 0.10. To assess gliosis, we determined total volume fraction of astrocyte cell bodies and fibers (Mouton et al, 2009). Volume fraction of astrocytes was quantified in a similar fashion as for myelin.…”
Section: Methodsmentioning
confidence: 99%
“…A study in 1997 showed the scatter plot of AD prevalence versus total food supply for countries; it further indicated that for every per capita additional grams of fat or calorie consumed per day, there is an average increase of 0.03% and 0.003%, respectively, in AD prevalence in the adult population of 65 years age or older (7). On the other hand, it has been shown that sustained CR reduces Aβ neuropathology compared with adlibitum feeding in several AD mouse models (11). Previous studies in which CR started in relatively young mice (<7months age) with transgenic APP mutations and relatively light amyloid loads demonstrated that CR blocks the mutation of Aβ-containing amyloid plaques (12).…”
Section: Cognitive Impairment and Calorie Restrictionmentioning
confidence: 99%